Complexos fosfínicos e suas aplicações na medicina - Queiroz, S. L.; Batista, A. A. (Soc Brasileira Quimica, 1996)
Phosphines are well known to chemists. The ligands themselves are widely used in organic synthesis (e.g. The Wittig reaction) and transition metal phosphine complexes have been studied extensively primarily for their applications as hydrogenation catalysts (e.g. Wilkinson's catalyst). In this article attention is focused on the biological properties of phosphines and metal phosphine complexes since the triethylphosphine Au(I) complex, auranofin, has been used as antiarthritic drug for clinical use. This fact has provided a stimulus for exploration of the biological chemistry of phosphines and their metal complexes. Metal phosphine complexes also offer potential as heart-imaging agents and anticancer drugs.
Phosphine complexes and their applications in medicine
Keywords: phosphines; complexes; biological properties